87.5k views
3 votes
PLEASE HELP!!! URGENT!

PLEASE HELP!!! URGENT!-example-1
User Dirck
by
5.2k points

1 Answer

6 votes

Answer:

(D)
p^(2) -9p+18

Explanation:

Assuming that the equation
x^(2) -2 = p, we can convert the equation into this.


p^(2) +18=9p

We can convert
9x^(2) -18 into 9p because
x^(2) -2 × 9 =
9x^(2) -18

Now we simplify this equation.

We can subtract 9p from both sides of the equation.


p^(2) +18-9p = 0

Re-ordering the equation gets us:


p^(2) -9p+18

So, (D)
p^(2) -9p+18 is equivalent to the original expression of
(x^(2) -2)^(2) + 18 = 9x^(2) -18

User All The Rage
by
5.6k points